2000
DOI: 10.1136/bjsm.34.1.35
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of lactate concentration in plasma collected from the toe, ear, and fingertip after a simulated rowing exercise

Abstract: The toe may offer a practical alternative for assessing the concentration of lactate during rowing, having the advantage that repeated blood samples can be removed without interruption of the rowing action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 21 publications
5
33
2
3
Order By: Relevance
“…In agreement with the findings of Dassonville et al (1998), Heller et al (1991, Feliu et al (1999) and Forsyth and Farrally (2000) the results in this rock climbing study indicate that before and after exercise fingertip capillary blood samples produce higher lactate concentrations than those taken from the ear lobe. The limits of agreement for each of the plots in Fig.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…In agreement with the findings of Dassonville et al (1998), Heller et al (1991, Feliu et al (1999) and Forsyth and Farrally (2000) the results in this rock climbing study indicate that before and after exercise fingertip capillary blood samples produce higher lactate concentrations than those taken from the ear lobe. The limits of agreement for each of the plots in Fig.…”
Section: Discussionsupporting
confidence: 95%
“…Possible explanations for these differences in rock climbing can be drawn from previous research. The differences in lactate concentrations between sampling sites observed in the studies by Dassonville et al (1998), Heller et al (1991), Feliu et al (1999 and Forsyth and Farrally (2000) have been attributed to a variety of factors including delays in release from localised sites of production into central circulation due to isometric contraction during exercise and reduced relative lower body involvement in exercise resulting in decreased lactate production at the toe. In the present study, the consistently higher blood lactate concentrations observed in the fingertip samples may well reflect localised production the result of isometric contraction essential to maintaining grip in rock climbing.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Removing blood from the toe enables the subject to carry on rowing, without interruption to the protocol (Forsyth and Farrally 2000). Samples were assessed immediately from lysed blood using a 1500 YSI lactate analyser (Yellow Springs Instruments, Ohio), which was calibrated with 5, 15 and 30 mmol l )1 standards.…”
Section: Analysis Of Variablesmentioning
confidence: 99%
“…После десетина минути од адекватнато спремање на испитаникот за претстојниот тест неопходно е да се отстрани нанесената маст (ресицата од увото се брише прво со вата натопена со алкохол, а потоа и со сува вата) [5][6][7]. По извршената дезинфекција, со стерилна ланцета се прави убод.…”
Section: вадење крв за испитувањеunclassified